Analisis dan Perancangan Sistem Informasi Administrasi RT/RW Berbasis Website Mengunakan Standar ISO/IEC 25010 - Agi Durega Durega; Novita Cindy Agustina; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2026)
This study aims to analyze and design a web-based RT/RW administrative information system to improve efficiency and transparency in neighborhood administrative management. The problems identified include resident data recording, letter management, and contribution payment processes that are still conducted manually, resulting in inefficiency and a high risk of errors. The research employed the Agile method with an iterative approach in system development. System modeling was carried out using Unified Modeling Language (UML), consisting of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. System testing was conducted based on the ISO/IEC 25010 standard, covering aspects of functional suitability, usability, reliability, and performance efficiency. The results indicate that the developed system functions properly, achieves a high usability level with an average score above 4 on a 5-point scale, and demonstrates responsive and stable performance. Therefore, the system is considered feasible as a solution for improving the quality of administrative services within the RT/RW environment.